Relações de hospitalidade/acolhimento no filó doméstico atual - o caso de Arvorezinha/RS/Brasil - Camilotto, Samara (My University, 2018)
The present study has as object of study of hospitality/welcoming relationships in domestic filó, in the form in which they are currently carried out. Having as referent the filó as a specific sociocultural practice of domestic encounter still carried out by descendants of Italian immigrants inside their residences; hospitality/welcoming from the socio-human perspective; and the municipality of Arvorezinha/RS as the target community of research, aims to analyze repercussions of the current sociocultural practice of filó in relation to intra-community social ties, considered relations of hospitality/welcoming. The research, in the case study modality, is defined as predominantly qualitative, with a hermeneutics approach. The analytic-interpretative process of the collected data was based on the enunciative discursive analysis associated to the content analysis. Semi-structured interviews were conducted with 25 residents of the municipality of Arvorezinha who participated in filós in the last five years, as welcomer or welcomed, considering a random process of indications. According to the voice of the interviewed people, the filó is a way of living together (meeting) constituted through a visit/reunion, which happens at night inside the residences, especially in the kitchens, congregating friends, neighbors and/or relatives, for the purpose of union, in which there is a conversation with exchanges of ideas and storytelling, card games, moments of expression of religiosity and food and drink offerings, and the guests are received by the hosts and, later, they return the practice, depending or not depending the previous invitation. The community appropriates the filó as a way of coexistence in which the cycle of encounters is not closed, without permeability. It is open to different groups of friends, neighbors and/or family interacting with each other and together, in a kind of network that connects in several points. In filós, one has the opportunity to make the (people) known more known and more convival. It also establishes itself as an opportunity to recognize yourself and to recognize yourself as a member of a community. In this sense, there are indications that this meeting, through its iterative cycle, strengthens the intracommunity social ties and maintains the practice, whose foundation of which is to welcome and be welcomed.
O presente trabalho tem como objeto de estudo relações de hospitalidade/acolhimento em filós domésticos, na forma como atualmente se realizam. Tendo por referente o filó como uma prática sociocultural específica de encontro no âmbito doméstico, ainda realizada por descendentes de imigrantes italianos no interior de suas residências; hospitalidade/acolhimento na perspectiva sócio-humana; e o município de Arvorezinha/RS como a comunidade-alvo de pesquisa, objetiva-se analisar repercussões da atual prática sociocultural do filó no que tange aos laços sociais intracomunitários, consideradas relações de hospitalidade/acolhimento. A pesquisa, na modalidade estudo de caso, define-se como predominantemente qualitativa, com abordagem hermenêutica. O processo analítico-interpretativo dos dados coletados pautou-se pela análise discursiva enunciativa associada à análise de conteúdo. Foram realizadas entrevistas semiestruturadas com 25 moradores do município de Arvorezinha que participaram de filós nos últimos cinco anos, como acolhedores ou acolhidos, considerando um processo randômico de indicações. De acordo com a voz dos sujeitos entrevistados, o filó é uma forma de convivência entre pessoas (encontro) constituída através de visita/reunião, que acontece à noite no interior das residências, sobretudo nas cozinhas, congregando amigos, vizinhos e/ou familiares, com a finalidade de união, em que ocorre conversa com trocas de ideias e relatos de histórias, jogos de cartas, momentos de expressão de religiosidade e oferta de alimentos e bebidas, sendo que os convidados são recebidos pelos anfitriões e, posteriormente, estes retribuem a prática, dependendo ou não de convite prévio. A comunidade se apropria do filó como um modo de convivência em que o ciclo dos encontros não é fechado, sem permeabilidade. Ele é aberto a diferentes grupos de amigos, vizinhos e/ou familiares interagindo entre si e uns com outros, numa espécie de rede que se conecta em diversos pontos. Em filós, tem-se oportunidade de tornar o (sujeito) conhecido cada vez mais conhecido e mais conviva. Também, institui-se como ocasião para (re)conhecer a si e se (re)conhecer como membro integrante de uma comunidade. Reúnem-se, nesse sentido, indícios de que esse encontro, pelo seu ciclo iterativo, fortalece os laços sociais intracomunitários e a manutenção da prática, cujo alicerce está no acolher e ser acolhido.
Keywords: Hospitalidade - Arvorezinha(RS); Cultura; Hospitality - Arvorezinha (Brazil); Culture